Tom and Jerry. Cowboy up! [videorecording (DVD)] - Van Citters, Darrell; Van Citters, Darrell (Warner Bros. Entertainment Inc., 2022)
The Wild, Wild West just got wilder with Tom and Jerry on the ranch. This time, the rivals team up to help a cowgirl and her brother save their homestead from a greedy land-grabber, and they're going to need some help. Jerry's three precocious nephews are all ready for action, and Tom is rounding up a posse of prairie dogs. But can a ragtag band of varmints defeat a deceitful desperado determined to deceive a damsel in distress? No matter what happens, with Tom and Jerry in the saddle, it'll be a rootin'-tootin' good time.